GEOGRAPHICAL LANDSCAPE CONDITIONS IN THE RESEARCH OF ARCHITECTURAL AND DESIGN SOLUTIONS OF UZBEKISTAN SANATORIUMS - A. Abdullayev (Journals Park Publishing, 2022)
As a person uses all the wealth and ornaments of the earth during his life, he must first of all know how to use the living and artificial nature that surrounds him correctly and wisely, depending on his needs. Only then will the human factor take its rightful place as a creator for the planet earth. For this, it is necessary to create the possibility of scientific analysis of the earth's layers, lithosphere and atmosphere.
Keywords: lithosphere, river landscape, delta landscape, island landscape, sea landscape, lake landscape.